Penyusunan Anggaran Operasional Pada UMKM Pocan - Anggraini, Ayu; Syam, Eka Widyawati; Tahir, Rafilah Uzdah; Adila, Adila Shabrina; Klarina, Adelia; Nur, Wildayana (Universitas Negeri Makassar, 2024)
ABSTRACTThis research article entitled